(3QSGdI GdZjHIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdbGgQ ddbOQ GdXGgQ dJCfjS GdUhQ GdefNQg ef GdYOe s
(3BNQgG (B:s
(3hbO CJGce efcQ hfcjQ hRYbG ajce CJJce GdUjMI JeJ hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B36s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds